2012
DOI: 10.1016/j.bbrc.2011.12.151
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heart failure on nucleolar organization and protein expression in human hearts

Abstract: Heart failure constitutes a major public health problem worldwide. The electrophysiological remodeling of failing hearts sets the stage for malignant arrhythmias, in which the role of the late Na + current (I NaL ) is relevant and is currently under investigation. In this study we examined the role of I NaL in the electrophysiological phenotype of ventricular myocytes, and its proarrhythmic effects in the failing heart. A model for cellular heart failure was proposed using a modified version of Grandi et al. m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 89 publications
(160 reference statements)
0
24
0
Order By: Relevance
“…We observed significantly increased levels of importins, exportins, Ran regulators and Nup62 in patients with this pathology, and a different configuration and morphology of the NPC [9]. We also observed changes in expression of nucleolin in patients with ICM and DCM, and these changes correlate with ventricular function [10]. In another study of our group, we showed that HF causes different changes in nuclear structure and function, observing changes in the levels of lamin A and C, proteins that maintain the structure of the nuclear lamina and organization of proteins such as emerin [25].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We observed significantly increased levels of importins, exportins, Ran regulators and Nup62 in patients with this pathology, and a different configuration and morphology of the NPC [9]. We also observed changes in expression of nucleolin in patients with ICM and DCM, and these changes correlate with ventricular function [10]. In another study of our group, we showed that HF causes different changes in nuclear structure and function, observing changes in the levels of lamin A and C, proteins that maintain the structure of the nuclear lamina and organization of proteins such as emerin [25].…”
Section: Discussionmentioning
confidence: 52%
“…Recently, we reported the effect of this syndrome on the nucleocytoplasmic trafficking machinery, such as increased importin, exportin, Ran regulators and Nup62 levels in ischaemic and dilated human hearts [9]. Furthermore, we demonstrated in these same HF patients changes in the morphology and organization of nuclear components with overexpression of nucleolin protein [10].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Neonatal rat cardiac myocytes treated with phenylephrine, an α1-adrenergic receptor agonist and stressed cardiac myocytes in the border zone of a myocardial infarction (MI) also display enlarged, irregularly shaped nucleoli [15]. An increase in nucleolar size concomitantly associated with alterations in the ultrastructure is observed during ischemic and dilated cardiomyopathies in humans, wherein nucleoli become less granular and more fibrillar, suggestive of increased ribosomal activity [16]. Nucleolar hypertrophy also results from polyploidy and endoreduplication of chromosomes [13].…”
Section: Nucleolus As a Stress Sensor In Cardiac Diseasementioning
confidence: 99%
“…Antibodies against cell surface Ncl inhibit angiogenesis in vitro and in vivo [38, 39]. Increases in Ncl protein expression and nucleolar localization are observed during ischemic and dilated cardiomyopathies, which also correlate with altered left ventricular dimensions and cardiac function [16]. Therefore as a pro-survival and pro-growth molecule, Ncl is involved in regulating the structure and function of the heart.…”
Section: Nucleolar Proteins Associated With Cardiac Pathophysiologymentioning
confidence: 99%